Cardiac arrhythmia prevalence in postmenopausal women - N. V. Izmozherova; A. N. Andreev; E. I. Gavrilova; A. A. Popov; M. I. Fominykh; E. V. Kozulina; E. A. Safyannik (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To study the prevalence and features of cardiac arrhythmias (CA) in postmenopausal women, as well as to investigate the CA association with carbohydrate metabolism disturbances. Material and methods. This cross-sectional study included 210 postmenopausal women (median age 57 years; age range 54,0-61,0 years). Median menopause duration was 7,9 years (3,0-12,0 years). The examination included Holter ECG monitoring, clinical evaluation, measurement of blood pressure, body mass index, waist and hips circumference the levels of glucose, insulin, lipids, Mg, Ca, uric acid, brain natriuretic peptide, and thyrotropin. Results. CA were registered in 99,5% of the participants, including ischemia (17,1%), supraventricular extrasystolia (88,1%), ventricular extrasystolia (VE; 53,8%), high-grade VE (HGVE; 21,5%), SV tachycardia paroxysms (19%), atrial fibrillation (2,3%), V tachycardia paroxysms (1,4%), asystolic periods (0,9%), sino-atrial and atrioventricular blocks (9,1%), bundle branch blocks (3,3%), sinus tachycardia (50,9%), and sinus bradycardia (23,8%). In postmenopausal women with disturbed carbohydrate metabolism, CA prevalence was higher for VE (1,9 times), HGVE (2,4 times), and polytopic VE (2,5 times). VE prevalence was higher in women with abdominal obesity and chronic pancreatitis. In addition, CA odds were higher in postmenopausal women with coronary heart disease (CHD; 2,75 times), chronic heart failure (CHF; 2,6 times), and acute cardiovascular events such as myocardial infarction or stroke (3,3 times). Conclusion. CA and ischemia prevalence was high in postmenopausal women, 21,5% of whom had high potential risk of sudden death. Increased odds of ventricular arrhythmias among postmenopausal women were associated with carbohydrate metabolism disturbances, CHD, CHF.